Food (is not) porn. Le immagini del cibo e l’orizzonte della scomparsa - Vagni, Tito (Mediascapes journal, 2017)
Starting from the analysis of the uninterrupted display of dishes and foods, defined by newspapers and scientific research with the word “food porn”, this paper proposes a reflection on the status of the contemporary image and its consumption. The article focuses on two different reflective lines of media images, one linked to Jean Baudrillard (1977) and the other to Susan Sontag (1977). The main objective is to verify the effectiveness of the Baudrillardian idea of proximity as a form of integral transparency, which is the basis of its definition of obscene. This paper argues that visual technology, especially photography and television, introduces a new way of seeing, extending their focus focused on the faculties of modern man. This mechanism does not produce full transparency, on the contrary it can favour a shrinking world and the disappearance of everything that is not within the scope of the lens. Therefore, this essays proposes the use of the concept of “food media” (Rousseau 2012) because it is able to take a more appropriately account of the food mediatisation process.